Предмет: Алгебра,
автор: kamalovamuza
Разложите на множители выражение :
с^2 - 4c + 4 - 9x^2
Ответы
Автор ответа:
0
1)с^2 - 4c + 4 - 9x^2=(с^2 - 9x^2)-(4с-4)=(с-3х)*(с+3х)-4*(с-1)
2)с^2 - 4c + 4 - 9x^2=(с^2 - 4c + 4) - 9x^2=(с-2)^2-9x^2
2)с^2 - 4c + 4 - 9x^2=(с^2 - 4c + 4) - 9x^2=(с-2)^2-9x^2
Автор ответа:
0
Это два способа ?
Похожие вопросы
Предмет: Математика,
автор: ribka811
Предмет: Английский язык,
автор: Аноним
Предмет: Русский язык,
автор: timca1908200874
Предмет: Математика,
автор: iromanka
Предмет: Физика,
автор: mariyasokolova